Implementation of User Centered Design on Interface Design for Mental Health Selfcare Services - Rizky Wira Pranata; Anisa Herdiani; Aristyo Hadikusuma (Universitas Budi Darma, 2022)
Mental health is essential in performing maximum activities. During the COVID-19 pandemic that is spreading all over the world. Some activities are transformed into a new activity called